SOSIALISASI DAN PELATIHAN PERANGKAT LUNAK MICROSOFT OFFICE DI LINGKUNGAN SEKOLAH DESA CURUG - Dwi Putra Espy Bendanu; Anjas Kosasih; Mia Audina; Ardila Putri Nur Karisma Dewi; Angga Kurnia; Unggul Prasetyo Utomo; Bayu Wibowo; Sutarto; Wenang Perdana; Muhammad Adam Febrian (Abdi Jurnal Publikasi, 2022)
Microsoft Office applications are very important to use in today's digital era, both for elementary school children to college and even for workers. For this reason, training activities are made in the context of community service, which aims to increase the knowledge and understanding of elementary school (SD) students in using Microsoft Office, especially Microsoft Word and Microsoft Excel. , training was made at SD NEGERI CURUG 1 with 30 students attending. Based on the training provided, the results showed that the participants looked very enthusiastic to take part in this training, on the other hand the lack of knowledge and training made elementary school students very difficult to operate it. After the training was carried out there were 90% of students who could understand and practice it, because the method we use is to guide students to practice what we convey. This training is very useful for elementary school students to add insight and knowledge about Microsoft Office Applications.